If Memory Serves: The effect of mental representations of size on prehension motions - Wilson, Stuart P (My University, 2009)
While previous studies have shown an effect of familiar size after recent exposure to an object (McIntosh & Lashley, 2008), this study aims to test the effect of object experience and potential mental representations that participants may hold. To do this expert tennis players are compared against non-tennis players. When presented with an oversized tennis ball (Type III) we predict that expert participants with greater prior knowledge of the standard sized tennis ball will significantly under scale and under reach in their prehension movements in comparison to participants who have minimal prior experience. This will be due to stronger mental representations they carry of the tennis ball. A number of kinematic measures were taken during non probe trials in order to predict movement behaviour for the Type III stimulus at probe distances. These predicted values were subtracted from actual values. Group effects on deviations from predicted values in Y axis displacement, peak velocity and maximum grip aperture were found to be non significant. Therefore it is not possible to infer any use of long term size mental representations on action guidance. These findings support those of Marotta & Goodale (2001) in that familiar size has no effect on action when participants have binocular vision available to them. These findings may also support Landy, Maloney, Johnston & Young’s (1995) theory of visual cue weighting, when binocular cues are available the weighting on vergence increases, rather than familiar size information being disregarded completely. It is suggested in future studies that non spherical stimuli are used and that the recent interaction effect found by McIntosh & Lashley (2008) is compared against any long term representations of size. In addition to this, significant differences in speed of motion displayed between expert and control groups could be tested in other action or perceptual-based tasks
Keywords: Visual Perception; Familiar Size